Renewable energy conversion, transmission, and storage - Sørensen, Bent, 1941- (Elsevier/Academic Press, 2007)
Strategies for the conversion, transmission and storage of renewable energy.
Keywords: Renewable energy sources.; elektronické knihy; electronic books